Il ruolo dell'informazione geografica nel settore dell'infomobility - Conti, Giuseppe; De Amicis, Raffaele (GEOmedia, 2008)
The role of geographical information in the field of infomobility Numerous studies highlight the important role infomobility will play in supporting the mobility of citizens, improving their safety, promoting the use of public transport, encouraging optimization within the transport system, and increasing energy efficiency and therefore reducing costs. The evolution of Location Based Service (LBS) in the field of infomobility will introduce a profound change to the way geographical information will be produced and shared. The greatest change will be initiated by the growth of location based social networks. This will have serious implications in terms of data accuracy, reliability and privacy.